Perancangan Kawasan Pendidikan Keterampilan Seni Bagi Anak Jalanan Dengan Konsep Arsitektur Tropis Di Kemayoran, Jakarta Pusat - Fortuna Bella Susanto; Karya Subagya; Harfa Iskandaria (MAESTRO, 2020)
The Art Skills Education Area is an area that serves as a place for street children to learn art skills, social skills, and be more flexible in their learning time, and it is hoped that this can be a form of overcoming street children in the city of Jakarta. The Art Skills Education Area for Street Children can also function as a place to showcase and sell some of the street children's art works that are educational, creative and recreational. The Art Skills Education Area is designed with a tropical architectural concept that is able to meet the needs of its users while still applying maximum comfort and a building that is able to adapt to the local environment. Keywords: Street Children, Jakarta, Tropical Architecture